Cavitation behind a circular micro pillar. (January 2018) - Nayebzadeh, Arash; Wang, Yingying; Tabkhi, Hanieh; Shin, Jeong-Heon; Peles, Yoav
Highlights: An experimental study, supported by numerical simulation, on hydrodynamic cavitation downstream a circular 150 µm pillar embedded in a microchannel was carried out. All cavitating flows were dominated by a distinct elongated cavity attached to the pillar pulsating along and across the microchannel. At higher Reynolds number, cyclic cavitation was observed prior to the formation of elongated cavity. Significant delays in the formation of cavitation and relatively low incipient cavitation numbers with respect to large scales were captured due to small bubble residence time, relatively high velocities, and the nature of the microchannel surface characteristics. The angle at which the minimum pillar pressure coefficient and flow separation was observed numerically compared well with the angle at which the vapor cavity was attached to the pillar, and the following relation was confirmed: θ C p, M i n . < θ S e p . < θ C a v . . Abstract: An experimental study of hydrodynamic cavitation was conducted in a rectangular microchannel with a pillar. Distilled water was used as working fluid in an open fluid loop, and cavitation was obtained by applying a range of pressure differences between inlet and outlet tanks. High speed camera captured the flow patterns from inception to fully developed cavitating flow. A minimum delay of 10 min in the formation of cavitation was recorded in all experiments, which is due to the stochastic nature of phenomenon. Cavitation inception conditions were obtained in terms of the cavitation numbers, and a flow map was developed for subsequent cavitation flow. By analyzing time series of gray scale intensity of pixels inside the cavity, dominant frequencies were identified. Transient single phase numerical simulations were performed to gain a better understanding of the flow field in the microchannel, verify pressure measurements, and to relate the separation angle to the attached cavitation angle around the pillar. Emphasis was placed on characterizing the wake region downstream the pillar as it is closely related to the occurrence of the cavitation phenomena.